P2X7 Receptor Signaling in Alzheimer’s Disease: A Critical Review of Mechanisms and Emerging (Asian Journal of Pharmaceutics (AJP), 2026)
Alzheimer’s disease (AD) is one of the most common causes of age-related memory impairment, progressively eroding an individual’s ability to retain personal memories, recognize familiar faces, and engage with daily life, while posing a substantial and growing burden on global healthcare systems. Extensive research has established that chronic neuroinflammation and neurodegenerative processes are central to AD pathophysiology, with increasing attention focused on the purinergic P2X7 receptor (P2X7R). This ligand-gated ion channel is markedly upregulated in AD and is implicated in multiple pathological events, including amyloid-β plaque accumulation, neurofibrillary tangle formation, microglial activation, excessive production of reactive oxygen species, and sustained inflammatory signaling. Through these interconnected mechanisms, P2X7R contributes to neuronal injury and progressive cognitive decline. Due to its central involvement in converging disease pathways, P2X7R has emerged as a promising therapeutic target. This review synthesizes current evidence on the role of P2X7R in AD pathogenesis and highlights emerging pharmacological strategies aimed at modulating this receptor, offering potential avenues for slowing disease progression and improving therapeutic outcomes in individuals with AD.